A new record of Holarctic genus Odontothrips (Thysanoptera, Thripidae) from India with a new species - Tyagi, Kaomud; Kumar, Vikas (Zootaxa, 2016)
The Holarctic genus Odontothrips of Megalurothrips genus-group was established by Amyot & Serville in 1843 with type species Thrips phaleratus Haliday (Mound & Palmer 1981, Mirab-balou & Chen 2011). This genus is known by 32 species from the Palearctic and Nearctic regions (ThripsWiki 2015), and these species are flower-living and mainly associated with flowers of family Fabaceae (Xie et al. 2010). The pest status of Odontothrips species is uncertain, but some species are reported to cause superficial damage to the flowers on which they feed. O. confusus Priesner is reported as a pest on lucerne in France and Czech Republic (Pitkin 1972), and also on legumes in Romania (Pustai et al. 2015). O. loti (Haliday) is reported as a major pest on Alfalfa in north China, where it feeds on tender leaves and causes leaf curling, whitening and withering (Kou et al. 2011).